Direct drive permanent magnet synchronous generator maximum tracking system based on model predictive torque active disturbance rejection control - YANG Ya; ZHU Qiang; XU Jie (Xi'an Gongcheng Daxue xuebao)
In order to better obtain wind energy, this article constructs a maximum power tracking control system based on model predictive torque active disturbance rejection, which is used for direct-drive permanent magnet synchronous generator (PMSG) to achieve maximum output power tracking of the system. In order to improve the response performance of PMSG and enhance the anti-interference performance of the system, this article first designed model predictive torque control (MPTC) for the current loop, and proposed a parameter compensation improved active disturbance rejection control (ADRC) strategy for the speed loop. This method inherits the advantages of ADRC and MPTC, and could effectively handle uncertainties such as internal and external interference, modeling errors, and wind speed variations to achieve maximum power tracking performance at different wind speeds. From the simulation results, it can be seen that when the wind speed changes slightly, the static error of the proposed control strategy speed is almost zero, while the error of the traditional MPTC control strategy is 0.2 rad/s. When the wind speed changes significantly, the error is small, and the error of the traditional MPTC control strategy reaches 5rad/s. The research results show that the proposed control method has better dynamic response performance and anti-interference performance than traditional controllers in maximum power tracking.